Expression of tumor antigens on primary ovarian cancer cells compared to established ovarian cancer cell lines - Kloudová, Kamila; Hromádková, Hana; Partlová, Simona; Brtnický, Tomáš; Rob, Lukáš; Bartůňková, Jiřina; Hensler, Michal; Halaška, Michael J; Špíšek, Radek; Fialová, Anna (Oncotarget, 2016)
In order to select a suitable combination of cancer cell lines as an appropriate source of antigens for dendritic cell-based immunotherapy of ovarian cancer, we analyzed the expression level of 21 tumor associated antigens (BIRC5, CA125, CEA, DDX43, EPCAM, FOLR1, Her-2/neu, MAGE-A1, MAGE-A2, MAGE-A3, MAGE-A4, MAGE-A6, MAGE-A10, MAGE-A12, MUC-1, NY-ESO-1, PRAME, p53, TPBG, TRT, WT1) in 4 established ovarian cancer cell lines and in primary tumor cells isolated from the high-grade serous epithelial ovarian cancer tissue. More than 90% of tumor samples expressed very high levels of CA125, FOLR1, EPCAM and MUC-1 and elevated levels of Her-2/neu, similarly to OVCAR-3 cell line. The combination of OV-90 and OVCAR-3 cell lines showed the highest overlap with patients' samples in the TAA expression profile.
Keywords: senioři; epiteliální ovariální karcinom; nádory glandulární a epitelové; nádorové buněčné linie; Gene Expression Profiling; immunotherapy; Neoplasms, Glandular and Epithelial; senioři nad 80 let; transkriptom; Middle Aged; nádory vaječníků; Adult; Cell Line, Tumor; Tumor Cells, Cultured; Transcriptome; Biomarkers, Tumor; Aged, 80 and over; ženské pohlaví; nádorové biomarkery; Antigens, Neoplasm; Humans; lidé středního věku; antigeny nádorové; stanovení celkové genové exprese; Carcinoma, Ovarian Epithelial; cancer cell lines; dospělí; high-grade serous epithelial ovarian cancer; tumor-associated antigens; Female; Aged; Ovarian Neoplasms; nádorové buňky kultivované; lidé